Sodium cation exchanged zeolites for direct air capture of CO2 - Do Yeong Kim; Wo Bin Bae; Haehyun Min; Kyeong-Hun Ryu; Sungjoon Kweon; Linh Mai Tran; Young Jin Kim; Min Bum Park; Sung Bong Kang (Applied Surface Science Advances)
Direct air capture technology requires investigating materials that can capture carbon dioxide inexpensively and efficiently, considering their performance under real atmospheric conditions. This study systematically investigated the CO2 adsorption-desorption performance of the representative zeolites (ZSM-5, Beta, Mordenite and Y) in H- and Na-forms using various analytical methods, including in-situ Diffuse Reflectance Infrared Fourier Transform spectroscopy. Compared to the corresponding H-zeolites, the enhancement of CO2 adsorption capacity by Na+ ions was observed for all the structure-type zeolite adsorbents. The Na-ZSM-5 showed excellent performance in the direct air capture of CO2 (DAC) due to its relatively smaller pore size and stronger acid-basic properties. The effective adsorption capacity of Na-ZSM-5 was pronounced at lower Si/Al ratios, making it the most efficient low-concentration CO2 adsorbent. The low silica Na-ZSM-5 exhibited a durable adsorption-desorption capacity after multiple cycles, indicating its practical reusability. When applied to real atmospheric air conditions, this low silica Na-ZSM-5 effectively adsorbed CO2 in the presence of oxygen and moisture, emphasizing its potential for a direct air capture adsorbent. This study provides insights into the properties of zeolites for CO2 capture from air, highlighting their potential as effective DAC sorbents that can be produced on a large scale.